Modulatory role for CCK-B antagonists in Parkinson's disease. - Boyce, S; Rupniak, N; Tye, S; Steventon, M; Iversen, S (1990)
We examined the ability of selective CCK-A and CCK-B receptor antagonists to induce or modulate the locomotor stimulant effects of dopamine agonists in MPTP-treated squirrel monkeys. Administration of 1-100 micrograms/kg i.p. of either the selective CCK-A receptor antagonist devazepide (MK-329) or the CCK-B receptor antagonist L-365,260 alone failed to stimulate a locomotor response in parkinsonian monkeys. In contrast, treatment with L-365,260 caused a 50-60% potentiation of the locomotor stimulatory effects of L-DOPA or (+)-PHNO. No such modulatory effects were observed following pretreatment with devazepide. We suggest that CCK-B receptor antagonists may be useful adjuncts to existing dopamine replacement therapy for improved management of Parkinson's disease.